Homosexual Orientation in Marriage: A Reason for Divorce? - Chrissutianto, Donny (Klabat Theological Review, 2020)
The number of homosexuals in Seventh Day Adventist Church has increased since 1980. It becomes a problem for the church until it was discussed and decided that this practice may as a reason for divorce. However, there is no hint if the case is homosexual in practice. If there is a problem in a newly couple that just married and in the very day one spouse says that he or she has the homosexual orientation what should be done with this couple. Is this confessing could be used as a reason for divorce? There should be a solution for the couple to handle this problem. The Bible clearly rejected homosexuality practices. To help the couple who has problem with homosexuality orientation in marriage, the principles of Bible and Spirit of prophecy should be utilized. This article attempts to expose these principles and helps to restore the proper sexual orientation that a couple should have in marriage.        Keywords: homosexual; divorce; marriage; sexual orientation